Transcriptional repression of the microphthalmia gene in melanoma cells correlates with the unresponsiveness of target genes to ectopic microphthalmia-associated transcription factor - Vachtenheim, J; Novotna, H; Ghanem, G (The Journal of investigative dermatology, 2001)
In the melanocyte, expression of genes required for pigment formation is mediated by the microphthalmia transcription factor, which is also critical for the development and survival of normal melanocytes during embryogenesis. Here we show that the expression of the melanocyte-specific isoform of microphthalmia transcription factor is lost in a subset of human melanoma cell lines, accompanied by the repression of tyrosinase and tyrosinase-related proteins 1 and 2, the three transcriptional target genes for microphthalmia. After the forced expression of microphthalmia transcription factor in melanoma cells where the expression of endogenous microphthalmia gene was found to be extinguished, no restoration of the melanogenic phenotype occurred and the transcription of the three microphthalmia transcription factor target genes remained silent. The transcription activation domain of microphthalmia transcription factor, tested as a GAL-MITF fusion protein, remained fully functional in these cells, however, and ectopic microphthalmia transcription factor localized normally to the nucleus and bound to the tyrosinase initiator E-box in gel retardation assays. Thus, the block of differentiation in microphthalmia-transcription-factor-negative melanomas extended the transcriptional repression of the microphthalmia transcription factor gene alone, and endogenous promoters in these melanoma cells became no longer responsive to microphthalmia transcription factor when this was substituted exogenously. The data presented suggest that a specific nuclear context is required for the transcriptional activation of the melanocyte markers by the microphthalmia transcription factor in malignant melanocytes and this specificity is lost concomitantly with the transcriptional repression of microphthalmia transcription factor.
Keywords: genetická transkripce; Microphthalmia-Associated Transcription Factor; nádory kůže; Cell Division; DNA-Binding Proteins; regulace genové exprese u nádorů; Humans; Skin Neoplasms; Tumor Cells, Cultured; proteiny; fungální proteiny; DNA vazebné proteiny; melanom; Transcription Factors; Saccharomyces cerevisiae - proteiny; Proteins; genetické markery; Transcription, Genetic; lidé; tyrosinasa; transkripční faktor spojený s mikroftalmií; Intramolecular Oxidoreductases; Membrane Glycoproteins; membránové glykoproteiny; nádorové buňky kultivované; Melanocytes; Saccharomyces cerevisiae Proteins; oxidoreduktasy; Peptide Fragments; Melanoma; melanocyty; Genetic Markers; peptidové fragmenty; transkripční faktory; terciární struktura proteinů; Gene Expression Regulation, Neoplastic; intramolekulární oxidoreduktasy; Monophenol Monooxygenase; Oxidoreductases; Protein Structure, Tertiary; Fungal Proteins; buněčné dělení